The Chican@ literary imagination: A collection of critical studies by Francisco A. Lomelí - Cañero, Julio (Universidad de Alcalá. Servicio de Publicaciones, 2012)
This book brings together several essays of one of the most productive and outstanding Chicano scholars, Francisco A. Lomelí. Even though teh book only gives a hint of the topics dealt with and covered by Professor Lomelí, it has tobe seen as a tribute to his fruitful career. The articles selected offer a broad view of his writings on the origins of Chicano/a literature and criticism and on Chicano/a authors, and they can serve as a countless source of information on Chicano Studies for future generations of researchers.